2015
DOI: 10.2174/1871527314666150429114040
|View full text |Cite
|
Sign up to set email alerts
|

Drug Targets of Migraine and Neuropathy: Treatment of Hyperexcitability

Abstract: Migraine and neuropathic pain are common causes of chronic pain. The exact pathomechanism has not been fully clarified for either disorder, but their pathophysiological backgrounds involve several similar mechanisms. Peripheral sensitization occurs in the neuronal elements of the dorsal root ganglion or the trigeminal ganglion, while central sensitization appears in the second-order neurons in the dorsal horn of the spinal cord or the trigeminal nucleus caudalis. Central neuronal hyperexcitability has been imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…21,22 It was noted that majority of these studies also found that θ and α band changes were in highest correlation with pain, and it was suggested by Pinheiro et al that increases in θ band power could serve as a biomarker in severe neuropathic pain. 23,20 We saw similar changes in all frequency bands. Yet, due to our sample size, it will take conducting a larger study perhaps with more than one pain modality to make any valid conclusion.…”
mentioning
confidence: 55%
“…21,22 It was noted that majority of these studies also found that θ and α band changes were in highest correlation with pain, and it was suggested by Pinheiro et al that increases in θ band power could serve as a biomarker in severe neuropathic pain. 23,20 We saw similar changes in all frequency bands. Yet, due to our sample size, it will take conducting a larger study perhaps with more than one pain modality to make any valid conclusion.…”
mentioning
confidence: 55%
“…Human and animal data show that migraine is presumably hyperexcitability disorder, which means that the glutamatergic system is overactive [ 7 ]. In addition, an increasing amount of evidence suggests that migraine could alsobe linked to the kynurenine pathway (KP) itself [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neuropathic sensory symptoms characterized by spontaneous or evoked pain is described as electric shock-like or burning, and other sensory disturbances such as paraesthesia, dysaesthesia, allodynia, hyperpathia or hyperalgesia. The symptoms of painful diabetic neuropathy (PDN) occur symmetrically in the distal parts of the extremities in an ascending manner [4,5] . The aetiology of NP involves a wide range of peripheral or central nervous system (CNS) disorders, including diabetic and other metabolic neuropathies, dysimmune neuropathies, postherpetic neuralgia, trigeminal neuralgia, human immundeficiency virus (HIV)-associated neuropathy or pain after spinal cord injury, poststroke pain, multiple sclerosis-associated pain or cancer-related pain [5] .…”
Section: Introductionmentioning
confidence: 99%
“…The symptoms of painful diabetic neuropathy (PDN) occur symmetrically in the distal parts of the extremities in an ascending manner [4,5] . The aetiology of NP involves a wide range of peripheral or central nervous system (CNS) disorders, including diabetic and other metabolic neuropathies, dysimmune neuropathies, postherpetic neuralgia, trigeminal neuralgia, human immundeficiency virus (HIV)-associated neuropathy or pain after spinal cord injury, poststroke pain, multiple sclerosis-associated pain or cancer-related pain [5] . Diabetes mellitus is a modern global medical challenge with an estimated prevalence of 366 million patients in 2030 [6] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation